Caracterização de jazidas para construção de habitações populares, com solo-cimento, em Santa Maria - Buriol, Telmo Luiz (2002)
The municipal district of Santa Maria presents an enormous deficiency in the attendance to the popular home, with poverty areas n busy for sub-houses, many irregular times. So that he tried to grow, in this work, studies as the use of available materials in the city and surroundings that they could be taken advantage of in the construction of popular houses, and that they go of low cost, besides the possibility of the use of the own population benefited with the labor in the execution of your houses. Where was pointed the possibility to develop the constructive technique with soil-cement, sees the presence of sandy soils in the city. Then samples of soils of six lied were removed, representing the geological formations that indicated more aptitude to the use. Of these, just the four beds of the formation Santa Maria (Basal sandstone) they presented results capable to promote the use. In this work it was observed resulted best when there were presents in the soil among 70-85% of sand, preferably non uniform and of larger grains, with clay presence among 5- 10% and of silt non superior to 20%, as well as index of inferior plasticity to 20%. For so much they studied lines, in weight, of 1/10, 1/12, 1/14 and 1/16, of cement in relation to the soil, these considered viable for production of solid bricks. At the end it was verified that the line of 1/10 just produced satisfactory results for the production of bricks, being considered cures for 7 days, although all the materials presented with rest absorptions below the allowed maxims.